2001
DOI: 10.1097/00002093-200107000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Caregiver Burden and Caregiver Health-Related Quality of Life in Alzheimer Disease

Abstract: The burden experienced by family caregivers of individuals with Alzheimer disease (AD) affects the caregivers' overall health-related quality of life (HRQOL). Assessing the influence on HRQOL is an integral part of determining the efficacy and economic attractiveness of interventions for AD. Generic preference-weighted instruments such as the Health Utilities Index Mark 2 (HUI2) are recommended for measuring HRQOL for cost-effectiveness studies. However, these instruments focus on physical attributes and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 37 publications
11
117
1
4
Order By: Relevance
“…Our results similarly confirm the impact of perceived caregiver burden on the deterioration of the caregiver's HRQL [13,34,35] . We have found that the severity of AD and dependence on a caregiver is inversely correlated to the caregiver's HRQL (general health) measured by the EQ-5D.…”
Section: Discussionsupporting
confidence: 86%
“…Our results similarly confirm the impact of perceived caregiver burden on the deterioration of the caregiver's HRQL [13,34,35] . We have found that the severity of AD and dependence on a caregiver is inversely correlated to the caregiver's HRQL (general health) measured by the EQ-5D.…”
Section: Discussionsupporting
confidence: 86%
“…Studies indicate that caring can place a significant level of burden on caregivers resulting in poorer physical and psychological wellbeing (Bell, Araki & Neumann, 2001;Gallagher-Thompson & Powers, 1997). This in turn can affect the care they provide, sometimes leading to premature institutionalisation of the person with dementia (PwD) (Bédard, Pedlar, Martin, Malott & Stones, 2000) or even elder abuse (Wolf, 1998).…”
Section: Caregiver Burdenmentioning
confidence: 99%
“…[1] Caregiver time increased for caregivers of AD-affected persons with more severe cognitive impairment. [13] EuroQoL (EQ-5D) is a standardized instrument used for quantifying health related quality of life based on visual analogic scale. This instrument has been developed since 1987 by the EuroQoL Group, and it is based on a descriptive model with 5 dimensions-mobility, self-care, usual activities, pain/discomfort, and anxiety/depression.…”
Section: Results Of the Reviewmentioning
confidence: 99%